Language Maintenance in Regional Languages : Sociolinguistic Study - Siregar, Indah wahyuni; Saragih, Zainuddin; Yudistira Hasibuan (CENDEKIA INDONESIA, 2025)
The problem currently facing regional languages is that their position and function no longer correspond to the position and function given to them. Regional languages are no longer used as a proud identity, and their function is no longer used as the main language of communication in the lives of families and their supporting communities. Therefore, it is necessary to maintain regional languages. This problem is related to the legacy of society's cultural values. If there is not a shred of culture that can be inherited by society, especially those whose languages are already extinct and almost extinct, then society will lose its cultural roots. This article discusses various efforts to maintain regional languages, so that benefits can be gained from efforts to maintain regional languages from various regions with different conditions.